Modeling of Sedimentation Process in the Irrigation Channel. (March 2017) - Tulus,; Situmorang, M
Abstract: Irrigation has been a central feature of agriculture for over 5, 000 years and is the method in which water is supplied to plants at regular intervals for agriculture. Channel irrigation allows irrigation over large areas, with large volumes of water. The content of the water in channel from the river generally contain a lot of material that can precipitate during the water flood the area of agriculture. This paper is to derive a mathematical model of sedimentation processes in the irrigation channel. The model is analysed using Finite Element Method with respect to the geometry of the channel in the district Galang, Sumatera Utara Province. From a computational point of view, results have shown the importance streamlines of the mixture velocity and the dispersed phase volume fraction.